Potential correlation between dental caries and intracranial aneurysm: an innovative prognostic marker for intracranial aneurysm development - Sun, Jia; Gui, Siming; Wei, Dachao; Jiang, Jia; Lin, Jun; Gong, Wentao; Ge, Huijian; Li, Youxiang (Frontiers in Neurology, 2025)
BackgroundThe prevalence of intracranial aneurysm (IA) in the population is approximately 3–7%, with a rupture mortality rate as high as 40%. Identification of risk factors for IA occurrence and provision of targeted preventive and therapeutic measures are crucial for clinical diagnosis of IA. Dental caries is a common oral disease that affects the global population. In this study, we aimed to explore the potential connection between dental caries and the incidence of IA.MethodsWe conducted a single-center retrospective 1:1 matched case-control study to assess the correlation between dental caries and the occurrence of IA among 230 participants. Participants were categorized into IA and non-IA groups. All participants underwent cerebral digital subtraction angiography or magnetic resonance angiography, as well as oral assessment. Using binary logistic regression analyses, we examined whether presence of dental caries was correlated with the occurrence of IA.ResultsCompared with the non-IA group, the IA group exhibited a greater prevalence of dental caries (90.44% vs. 56.52%) and a greater prevalence of history of root canal treatment (73.91% vs. 48.70%). Multiple logistic regression analysis revealed a significance between the presence of dental caries (OR: 4.14, 95% CI: 1.35–12.66) and IA occurrence. Also, the history of root canal treatment (OR: 2.03, 95% CI: 1.09–3.79) were significantly associated with IA occurrence (all p < 0.05).ConclusionDental caries was significantly associated with the incidence of IA. Cariogenic bacteria may enter the systemic circulation through pulp, potentially leading to pathological changes in normal cerebral blood vessels, such as the development of IA.